Inoganic crystallization: a bibliometric analysis (Research, Society and Development, 2019)
Inorganic fouling of calcium carbonate in reservoir rock grains and production lines is a recurring problem in the oil industry, especially in the pre-salt.. In order to determine which mechanisms have the greatest influence on the formation of crystals and the conditions that promote them, a bibliometric study was carried out at the SCOPUS® base, analyzing the volume of publications in the area and the most recent contributions on crystallization processes. The search started with articles that contained the words "Crystallization of Calcium Carbonate", after a refinement, were selected the 5 more recent studies. As results, the aggregation was pointed as the mechanism of greater influence in the pore clogging and, consequently, reduction in the permeability of the porous rock. This change in permeability decreases the amount of oil produced and causes losses in production. Another mechanism pointed out was the growth of crystals, which can be inhibited by means of ultrasonic techniques.